1999
DOI: 10.1097/00001756-199901180-00018
|View full text |Cite
|
Sign up to set email alerts
|

Grape polyphenols protect neurodegenerative changes induced by chronic ethanol administration

Abstract: Increased oxidative stress in the brain due to chronic ethanol consumption is known to result in a number of neurodegenerative changes. This study was designed to test whether dietary supplementation of grape polyphenols (GP) can offer protection to the neurodegenerative changes resulting from chronic ethanol consumption. Sprague-Dawley rats were fed a Leiber-DeCarli liquid diet with ethanol or isocaloric amount of maltose, and with or without GP for 2 months. Chronic ethanol caused significant decreases in sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…Furthermore, flavonoids showed protective effects against an increase in brain lipid peroxidation following Vitamin E deprivation [219], attenuated neuronal damage induced by ethanol administration [113,199] and reduced O-ethyl-S,Sdipropyl phosphorodithioate-induced neurotoxicity in mice [163]. Interestingly, the oral administration of a catechincontaining antioxidant preparation significantly increased the life span of senescence-accelerated mice [112] and increased SOD activity in the mitochondrial fraction of the striatum and the midbrain, decreased products of lipid peroxidation in cortex and cerebellum, and attenuated the iron(II) chloride-induced formation of markers of DNA damage in the cortex of aged rats [106].…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…Furthermore, flavonoids showed protective effects against an increase in brain lipid peroxidation following Vitamin E deprivation [219], attenuated neuronal damage induced by ethanol administration [113,199] and reduced O-ethyl-S,Sdipropyl phosphorodithioate-induced neurotoxicity in mice [163]. Interestingly, the oral administration of a catechincontaining antioxidant preparation significantly increased the life span of senescence-accelerated mice [112] and increased SOD activity in the mitochondrial fraction of the striatum and the midbrain, decreased products of lipid peroxidation in cortex and cerebellum, and attenuated the iron(II) chloride-induced formation of markers of DNA damage in the cortex of aged rats [106].…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…Catechin and epicatechin have been shown to reduce ischemia and reperfusion injury in gerbils (71). Although these compounds (interestingly present in dark chocolate as well) possess potent antioxidant capacities, they also increase superoxide dismutase activity and have been shown to protect against brain lipid peroxidation (61,72).…”
mentioning
confidence: 99%
“…However, this protective effect has not been confirmed in other studies [249,250]. There is enough experimental evidence [212][213][214][215][216][217] that red wine consumption may be beneficial in the prevention of age-related neurodegenerative disorders such as PD.…”
Section: Alcohol Consumptionmentioning
confidence: 88%
“…Epidemiological studies have shown that moderate wine consumption can be protective against neurological disorders such as age-related macular degeneration [211]. Moreover, in vitro and in vivo pre-clinical studies have shown the neuroprotective effect of lyophilized red wine [212], grape polyphenols [213], quercetin [214], transresveratrol [212,215,216], and (+)-catechin [217]. There is also increasing interest for the role of tea (Camellia sinensis) in maintaining health and in treating disease.…”
Section: Dietary Supply Of Antioxidantsmentioning
confidence: 99%